A model for knowledge portal to support communities of practice - Ismail, Aisyah (2011)
Communities of practice (CoP) are groups of individuals with common interest who communicate and share knowledge among their respective group. The use of knowledge portals for CoP will assist the exchange of knowledge, thus it promotes the learning process. Nevertheless, such portals may encounter many challenges to draw the interest among the members in sharing their knowledge voluntarily. As the result, the portals face inactive participants among the members. Knowledge sharing system such as knowledge portal is useless without knowledge sharing activity among its members. In order to encourage users to share their knowledge, we first must uncover the underlying problems on why the users are reluctant to share their knowledge through the knowledge sharing system. This paper reviews the current obstacles in knowledge sharing among CoP and proposes a model to support the needs that software engineers may consider when designing a knowledge portal.